Treg in inborn errors of immunity: gaps, knowns and future perspectives - Kennedy-Batalla, Rebeca; Acevedo, Daniel; Luo, Yiyi; Esteve-Solé, Ana; Vlagea, Alexandru; Correa-Rocha, Rafael; Seoane-Reula, Ma Elena; Alsina, Laia (Frontiers in Immunology, 2024)
Regulatory T cells (Treg) are essential for immune balance, preventing overreactive responses and autoimmunity. Although traditionally characterized as CD4+CD25+CD127 low FoxP3 hi , recent research has revealed diverse Treg subsets such as Tr1, Tr1-like, and CD8 Treg. Treg dysfunction leads to severe autoimmune diseases and immune-mediated inflammatory disorders. Inborn errors of immunity (IEI) are a group of disorders that affect correct functioning of the immune system. IEI include Tregopathies caused by genetic mutations affecting Treg development or function. In addition, This is a provisional file, not the final typeset article Treg dysfunction is also observed in other IEIs, whose underlying mechanisms are largely unknown, thus requiring further research. This review provides a comprehensive overview and discussion of Treg in IEI focused on: A) advances and controversies in the evaluation of Treg extended subphenotypes and function; B) current knowledge and gaps in Treg disturbances in Tregopathies and other IEI including Treg subpopulation changes, genotype-phenotype correlation, Treg changes with disease activity, and available therapies, and C) the potential of Treg cell-based therapies for IEI with immune dysregulation. The aim is to improve both the diagnostic and the therapeutic approaches to IEI when there is involvement of Treg. We performed a non-systematic targeted literature review with a knowledgeable selection of current, high-quality original and review articles on Treg and IEI available since 2003 (with 58% of the articles within the last 6 years) in the PubMed database.